Optofluidic Sensor: Evaporation Kinetics Detection of Solvents Dissolved with Cd3P2 Colloidal Quantum Dots in a Rolled‐Up Microtube. Issue 2 (14th November 2014) - Miao, Shiding; Chen, Dechao; Madani, Abbas; Jorgensen, Matthew R.; Bolaños Quiñones, Vladimir A.; Ma, Libo; Hickey, Stephen G.; Eychmüller, Alexander; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> A method for measuring the evaporation kinetics of pure solvents and solutions containing Cd3P2 quantum dots (QDs) in SiO/SiO2 rolled‐up microtube (RUT) resonators is reported. The QDs serve as wavelength‐tunable fluorescent sources for the RUT resonator. The first‐order kinetic constant (295 K) of the evaporation of toluene embedded in a RUT (D = 9.10 μm) is evaluated (0.055 min−1). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>